Interrupting chains of respiratory infections via remote patient monitoring in ambulatory care - a randomized controlled trial during the 2020/21 infection season - Sarah Eichler; Sebastian Carnarius; Edgar Steiger; Dominik von Stillfried (Elsevier, 2022)
Aim of the study: The aim of the study was to investigate patient satisfaction, saving of time and the possible reduction of visits to medical practices that use Remote Patient Monitoring (RPM) during treatment compared to usual care. Methods: In a randomized controlled trial between October 2020 and May 2021, the participating medical practices were randomized into three groups (two different RPM systems, one control). Doctors were required to enroll patients ≥18 years with acute respiratory infection in possession of a web-enabled device, such as a laptop, tablet or computer. After a three-month study phase, doctors were asked to describe the treatment of their patients via online survey. Patients were also questioned. The analysis was carried out descriptively and through group comparisons. Results: 51 practices with 121 patients were included. Overall, the results generally show a positive assessment of digital care on the patient side. As for the doctors, handling and integrating the systems into established practice routines seem to be a challenge. Further, the number of patient visits to the medical practice was not reduced by using the systems. Doctors did not save time, but the relationship to the patients was intensified. Conclusion: While there was no indication for an increase in efficiency by using RPM systems, participating doctors indicated their potential for an enhanced interaction between doctor and patient. In particular, intensified interaction contact with patients with chronic diseases (e. g. COPD, long-COVID) could be of long-term interest and importance for doctors in ambulatory care.Trial Registration: DRKS00023553.